Across the Sahara Tracks, Trade and Cross-Cultural Exchange in Libya - Braun, Klaus; Passon, Jacqueline (Springer International Publishing : Imprint: Springer, 2020)
This open access book provides a multi-perspective approach to the caravan trade in the Sahara during the 19th century. Based on travelogues from European travelers, recently found Arab sources, historical maps and results from several expeditions, the book gives an overview of the historical periods of the caravan trade as well as detailed information about the infrastructure which was necessary to establish those trade networks. Included are a variety of unique historical and recent maps as well as remote sensing images of the important trade routes and the corresponding historic oases. To give a deeper understanding of how those trading networks work, aspects such as culturally influenced concepts of spatial orientation are discussed. The book aims to be a useful reference for the caravan trade in the Sahara, that can be recommended both to students and to specialists and researchers in the field of Geography, History and African Studies.